Predicting the risk of dental implant loss using deep learning. (9th July 2022) - Huang, Nannan; Liu, Peng; Yan, Youlong; Xu, Ling; Huang, Yuanding; Fu, Gang; Lan, Yiqing; Yang, Sheng; Song, Jinlin; Li, Yuzhou
Abstract: Aim: To investigate the feasibility of predicting dental implant loss risk with deep learning (DL) based on preoperative cone‐beam computed tomography. Materials and Methods: Six hundred and three patients who underwent implant surgery (279 high‐risk patients who did and 324 low‐risk patients who did not experience implant loss within 5 years) between January 2012 and January 2020 were enrolled. Three models, a logistic regression clinical model (CM) based on clinical features, a DL model based on radiography features, and an integrated model (IM) developed by combining CM with DL, were developed to predict the 5‐year implant loss risk. The area under the receiver operating characteristic curve (AUC) was used to evaluate the model performance. Time to implant loss was considered for both groups, and Kaplan–Meier curves were created and compared by the log‐rank test. Results: The IM exhibited the best performance in predicting implant loss risk (AUC = 0.90, 95% confidence interval [CI] 0.84–0.95), followed by the DL model (AUC = 0.87, 95% CI 0.80–0.92) and the CM (AUC = 0.72, 95% CI 0.63–0.79). Conclusions: Our study offers preliminary evidence that both the DL model and the IM performed well in predicting implant fate within 5 years and thus may greatly facilitate implant practitioners in assessing preoperative risks.